"Palpandi corporis et contrectandi vulneris obtulit facultatem" (Trin. III 20). La exégesis de Jn 20,24-29 en la obra de Hilario de Poitiers a la luz de la tradición precedente - Alba López, Almudena (Vox Patrum, 2025)
The main patristic witnesses assume that Thomas touched the body of Christ in order to verify the truth of his resurrection, even though this contact by the disciple is not stated in the Johannine account. By refusing to alter the original account, Hilary of Poitiers does not attributed an action that is not documented by the Gospel to the apostle and highlights the fact that the Son adapts to the weakness of man’s intelligence, providing an answer to unbelievers using the motif of doubting Thomas to reflect on the transformative effect of miracles and the soteriological function of faith.